A transport model describing how defect accumulation leads to intrinsic dielectric breakdown and post-breakdown conduction. (January 2022) - Xu, Yueming; Lu, Toh-Ming; Plawsky, Joel L.
Abstract: A charge transport model, originally developed for simulating time-dependent dielectric breakdown (TDDB) behavior at the interconnect level, was modified and extended to also apply to the current-voltage (I-V) behavior in the post-breakdown region. The model allows one to simulate the current-voltage characteristics of the dielectric material from its pristine state, through the wear-out and breakdown phase, and into the post-breakdown region. The systematic transition from the insulator region to the conductor-like region is visualized through the intrinsically generated trap distribution evolution. A percolation starts forming near the anode at a critical trap concentration of 5  ×  10 26 m − 3 for the system under study and proceeds directionally, towards the cathode. Soft breakdown occurs when the percolation path front reaches the cathode with a trap volume fraction of 0.15, close to the theoretical value of 0.16. Hard breakdown, at the switching point, is associated with the completion of a vacancy-type percolation path and saturation of the trap concentration. A power law relationship with a power of 2 is found between the system's conductance and the trap concentration near the anode between the critical point and the switching point. A predicted linear post-breakdown region following the breakdown event along with a weak temperature dependence agrees well with experimental observations. Highlights: Finite-element-method simulation of intrinsic dielectric breakdown process Current-voltage predictions from insulating through fully conducting states Trap generation and de-trapping via tunneling provide a percolation path. Breakdown behavior characterized by trap density and percolation thresholds. Temperature dependence pre and post breakdown agree qualitatively with experiment.